A Hybrid Mean Value Involving the Two-Term Exponential Sums and Two-Term Character Sums - Liu Miaohua; Li Xiaoxue (Journal of Applied Mathematics)
The main purpose of this paper is using the properties of Gauss sums and the estimate for character sums to study the hybrid mean value problem involving the two-term exponential sums and two-term character sums and give an interesting asymptotic formula for it.